2022
DOI: 10.3389/fnut.2022.899255
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Calorie Restriction Improves Lipid Metabolism and Aggravates Inflammation in the Liver of Old Wistar Rats

Abstract: Aging is a progressive process that could disturb metabolic homeostasis in the liver via ectopic lipid accumulation, oxidative stress, and deterioration of inflammatory response. Although calorie restriction (CR) is recognized as beneficial for life span and health span prolongation, it is still unclear how late-onset CR, characterized by late beginning and short duration, affects age-related processes. The aim of this study was to examine how late-onset CR-induced metabolic adjustments impact lipid status and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
2
3
1
Order By: Relevance
“…The ability of DR to preserve Δψ m during early aging does not appear to involve the activity of UCPs, but instead requires both mitochondrial ANT and IF1 activity. We also find that fatty acid metabolism is required for preservation of Δψ m by DR, consistent with a recent report in worms that fatty acid metabolism promotes longevity [21], as well as numerous studies in mammals showing that DR increases fatty acid oxidation [36, 47-49]. While it remains difficult to quantify or control Δψ m in vivo in mammals, this work should serve to orient future experiments to define mechanisms underlying these observations in worms and other systems.…”
Section: Discussionsupporting
confidence: 92%
“…The ability of DR to preserve Δψ m during early aging does not appear to involve the activity of UCPs, but instead requires both mitochondrial ANT and IF1 activity. We also find that fatty acid metabolism is required for preservation of Δψ m by DR, consistent with a recent report in worms that fatty acid metabolism promotes longevity [21], as well as numerous studies in mammals showing that DR increases fatty acid oxidation [36, 47-49]. While it remains difficult to quantify or control Δψ m in vivo in mammals, this work should serve to orient future experiments to define mechanisms underlying these observations in worms and other systems.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, short-term CR markedly reduced the body weight of the animals and, in line with previous studies, led to a plethora of changes to the hepatic microenvironment [ 20 , 46 , 47 , 48 ]. Overall, short-term CR failed to revert the release of inflammation-related cytokines and LM to levels found in young animals.…”
Section: Discussionsupporting
confidence: 90%
“…However, the changes were not significant in the second week in both sexes. Previous evidence from different species suggested that dietary restriction can reduce triglyceride levels (Mahoney et al, 2006;Teofilović et al, 2022;Zhan et al, 2007). Triglycerides are mainly derived from dietary sources, particularly from dietary fats and carbohydrates via the liver (Havel et al, 1962).…”
Section: Discussionmentioning
confidence: 99%